Utilizing Detectron2 for accurate and efficient colon cancer detection in histopathological images - Chen, Luxi; Shen, Jie; Li, Xinyu; Li, Rongzhou; Gao, Xiaoyun; Chen, Xinyue; Pan, Xiaotian; Jin, Xiaosheng (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionColon cancer ranks among the most prevalent and lethal cancers globally, emphasizing the urgent need for accurate and early diagnostic tools. Recent advances in deep learning have shown promise in medical image analysis, offering potential improvements in detection accuracy and efficiency.MethodsThis study proposes a novel approach for classifying colon tissue images as normal or cancerous using Detectron2, a deep learning framework known for its superior object detection and segmentation capabilities. The model was adapted and optimized for histopathological image classification tasks. Training and evaluation were conducted on the LC25000 dataset, which contains 10,000 labeled images (5,000 normal and 5,000 cancerous).ResultsThe optimized Detectron2 model achieved an exceptional accuracy of 99.8%, significantly outperforming traditional image analysis methods. The framework demonstrated high computational efficiency and robustness in handling the complexity of medical image data.DiscussionThese results highlight Detectron2’s effectiveness as a powerful tool for computer-aided diagnostics in colon cancer detection. The approach shows strong potential for integration into clinical workflows, aiding pathologists in early diagnosis and contributing to improved patient outcomes. This study also illustrates the transformative impact of advanced machine learning techniques on medical imaging and cancer diagnostics.